PENERAPAN DETEKSI DINI KANKER SEVIKS DI TEMPAT HIBURAN KABUPATEN KARAWANG - Eneng Solihah; Ugi Sugiarsih; Warliana Warliana (Poltekkes Kemenkes Bandung, 2022)
DA Karaoke and restaurant is one of the many entertainment venues in Karawang Regency, which is located in the center of the city. Almost all the female employees of the DA entertainment venues are women. 65% of the female employees in that place work as song guides (PL) at karaoke, with a lifestyle almost 58% are active smokers and consume liquor and 100% are passive smokers and sometimes have free sex or in other words as female sex workers (WPS). FSW is a group of women who are at high risk of cervical cancer. The risk will increase in women who have sexual relations at the age of less than 16 years, a history of more than four births, having more than six sexual partners increases the risk 10 times, active smokers increase the risk two and a half greater and passive smoking increases one point four. (Vet et all, 2008). The data above shows that there is a susceptibility to the incidence of cervical cancer caused by free sex behavior, which is clearly the target of having sex with many partners (multi-partners), active smokers and consuming alcoholic beverages.